(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Growing vegetables has a significant impact on the biological, chemical and physical characteristics of the soil around. Heavy metal contamination of soil is now a global issue that reduces agricultural productivity, degrades the nutritional value of vegetables, and poses a risk to human health once they enter the food chain. In present study, analyses the concentration of heavy metals (Fe, As, Cr, Cu, Cd, Pb, Hg, and Zn.) of common vegetables i.e., Solanum lycopersicum (Tomato), Solanum melongena (Brinjal) and respective soil samples obtain from the Korba Region, India are described. The concentration of Fe, As, Cr, Cu, Cd, Pb, Hg and Zn in the soil was ranged from 880-1540, 109-184, 75-82, 79.20-172, 0.62-1.52, 92-204, 0.28-0.42 and 172-222 mg/kg respectively. Results indicate the heavy metals concentration were generally higher Fe>Zn>Pb>As>Cu>Cr>Cd>Hg, indicating the need for immediate action to reduce contamination rates and identify the serious problem of heavy metal pollution in this area.